The nature of superfuidity and Bose-Einstein condensation: from liquid ⁴He to dilute ultracold atomic gases (Review Article) - Vilchynskyy, S.I.; Yakimenko, A.I.; Isaieva, K.O.; Chumachenko, A.V. (Физика низких температур, 2013)
We present a brief overview of crucial historical stages in creation of superfluidity theory and of the current
state of the microscopic theory of superfluid
⁴He. We pay special attention to the role of Bose-Einstein condensates
(BECs) in understanding of physical mechanisms of superfluidity and identification of quantum mechanical
structure of
⁴He superfluid component below -point, in particular — the possibility that at least two types of
condensates may appear and coexist simultaneously in superfluid
⁴He. In this context we discuss the properties
of the binary mixtures of BECs and types of excitations, which may appear due to intercomponent interaction in
such binary mixtures of condensates. We also discuss current status of investigations of persistent currents in toroidal
optical traps and present an outlook of our recent findings on this subject.